The Role of E-Commerce in Improving the Economic Walfare of Society in the Digital Age - Sri Astuti; Nova Ayu Maharany; Ahmad Raihan Wildan; Ammar Firmansyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Indonesia as one of the developing countries that Pancasila economic system must utilize new digital technologies to improve its economy, improve its economiy. This research aims to understand the role of e-commerce in improving people’s walfare in the digital era. It explores how the digital economy has impacted the growth of online commerce businesses in Indonesia over the past five years and examines the digital strategies adopted by e-commerce companies to improve operational efficiency and customer service. Operational efficiency and customer service. The study highlights the contribution of leading platforms such as Shopee and Tokopedia, which are use advanced digital marketing tehcniques, user-friendly interfaces and strong security measures to build trust, and strong security measures to build consumer trust and increase engagement. Financial technology (fintech) also plays an important role in supporting e-commerce by enabling transaction role in supporting e-commerce by enabling secure transactions, efficient transactions, and expanding access to financial services. In summary, the growth of combined internet usage, e-commerce, and fintech in Indonesia highlights the country’s significant strides in developing a dynamic digital economy. The country’s significant strides in developing a vibrant digital economy. These advancement are diving economic growth, enhancing financial inclusion, and transform the shopping experience, thereby improving the overall economic well-being of society as a whole in the digital age